Determination of shakedown boundary and fitness-assessment-diagrams of cracked pipe bends - ElSaadany, Mostafa (AUC Knowledge Fountain, 2012)
Determination of shakedown boundaries of 90-degree defect-free smooth pipe bends has received substantial attention by several researchers within the recent decades. However, scarce information is found within the literature regarding the determination of the shakedown boundary of cracked pipe bends. The current research outcomes include the determination of shakedown boundary for a circumferentially cracked 90-degree pipe bend via a simplified technique utilizing the finite element method, and introduction of Failure-Assessment-Diagrams (FAD) in compliance with the API 579 Failure-for-Service assessment of pressure vessel and piping components. The analyzed cracked pipe bend is subjected to the combined effect of steady internal pressure spectrum and cyclic In-Plane Closing (IPC) or opening (IPO) bending moments. Line Spring Elements (LSE) are embedded in quadratic shell elements to model part through cracks. Failure assessment diagrams (FAD) are developed through linking the J-integral fracture mechanics parameter with the shakedown limit moments of the analyzed cracked 90-degree pipe bend. The LSE outcomes illustrated satisfactory results in comparison to the results of verification studies: stress intensity factor, Shakedown (SD) limit, and limit load. Additionally, full elastic-plastic cyclic loading finite element analyses are conducted and the outcomes revealed good correlation with the results obtained via the simplified technique. The maximum load carrying capacity (limit moment) and the elastic domain are also computed thereby generating a Bree diagram for the cracked pipe bend.